Exploring Students’ Use of Chatbot AI for Solving Grammar Tasks - Erma Rahayu Lestari; Banu Wicaksono (Departement of Mathematics Education, 2023)
Due to the emergence of artificial intelligence technologies, chatbots have gained significant traction in diverse sectors, encompassing education. Within the English education department specifically, the use of chatbots for grammar tasks has been a topic of interest. This study aims to investigate how students utilize the chatbot ChatGPT to solve grammar tasks assigned by their lecturer. The grammar tasks given to the students were in multiple-choice, dialogue and paragraph gap filling, and picture series story tasks. These tasks were closely integrated with the writing skills component and were completed by 28 first-year English Education Department students. This qualitative study was conducted through reflective reports and in-depth interviews with the participants. The study found that there were three distinct methods of utilizing ChatGPT to solve grammar tasks. The first method was copy-pasting, where students would simply copy and paste the required sentences into the chatbot for an automated response. The second method, L1 L2 translation, involved translating sentences of their response from their native language into English using the chatbot. The third method, detail-directed instruction, involved students providing specific instructions to the chatbot on how they wanted their response to be formatted.